Composite coatings of chitosan and alginate emulsions with olive oil to enhance postharvest quality and shelf life of fresh figs (Ficus carica L. cv. Pingo De Mel) - Vieira, Tiago M. (2022)
Fresh figs are very appreciated and have been associated with health benefits. However, these fruits are highly perishable. In this study, edible coatings were studied envisaging their positive effect in enhancing figs’ shelf-life. Fig fruits cv. ‘Pingo de mel’ were harvested at commercial ripening stage and single emulsion-based coatings, composed of chitosan + olive oil and alginate + olive oil, were applied. After coatings application by dipping each fruit in the emulsion-based solutions at 4 C and drying, the coated fruits were sprayed with crosslinking solutions (6% tripolyphosphate and 1% calcium chloride for chitosan and alginate-based coatings, respectively). Then, were maintained at 4 C and analyzed after 1, 7, 14 and 19 days of storage. After each time interval, fruits were further maintained at 25 C for 2 days. The results have shown that coatings were effective on delaying fungal decay and postharvest ripening indicators (respiration rate, mass loss, softening and total soluble solids/titratable acidity ratio). The results foresee a fruits’ shelf life between 14 and 19 days under refrigeration at 4 C that may be followed up to 2 days at ambient temperature, higher than that estimated for uncoated fruits (less than 14 days at 4 C plus to 2 days at ambient temperature)